2017
DOI: 10.1111/jfbc.12399
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of α-glucosidase inhibitory compounds fromPhaleria macrocarpafruit flesh using solvent, sonication, and subcritical carbon dioxide soxhlet methods

Abstract: The objective of this study was to compare α‐glucosidase inhibitory activity of Phaleria macrocarpa extracts using subcritical carbon dioxide (subCO2) soxhlet extraction method with sonication and solvent extraction methods. The extraction was performed by subCO2 soxlet using carbon dioxide and the conventional organic solvent‐based sonication using ethanol and water, solvent extraction using methanol, and n‐hexane solvents. The yields and α‐glucosidase inhibitory activity of the P. macrocarpa extracts were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Thus metabolites that were playing roles as phytochemical markers may be suggested. The model diagnostic of the PLS model developed can be evaluated using several parameters such as goodness of fit, a test of permutation, and the capability of the model to predict the value using actual to predicted plot [18]. The cumulative values of R2Y explain the goodness of fit is indicating the percentage of variation of the response explained by the model, and the cumulative value of Q 2 Y is representing the percentage of the variation of the response predicted by the model according to cross-validation [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus metabolites that were playing roles as phytochemical markers may be suggested. The model diagnostic of the PLS model developed can be evaluated using several parameters such as goodness of fit, a test of permutation, and the capability of the model to predict the value using actual to predicted plot [18]. The cumulative values of R2Y explain the goodness of fit is indicating the percentage of variation of the response explained by the model, and the cumulative value of Q 2 Y is representing the percentage of the variation of the response predicted by the model according to cross-validation [13].…”
Section: Resultsmentioning
confidence: 99%
“…α -Glucosidase inhibition assay was performed according to Collins et al [18], Deautschländer et al [19], and Sajak et al [20] with slight modification. The reaction mixtures consisting 10 μ L of the test sample (0.078-5 mg/mL), 130 μ L of 30 mM of phosphate buffer solution (pH 6.5), and 10 μ L of α -glucosidase working solution were incubated at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…However, these are energy intensive techniques, and they depend largely on concentrated toxic organic solvents, which may pose environmental concerns. Different innovative extraction techniques including ultrasound, supercritical fluid (SFE), microwave, and subcritical CO 2 -assisted (SubCO 2 ) methods are being developed for the recovery of biologically valuable components from various plant matrices [ 9 , 10 , 11 ]. The supercritical state was first known back in 1822 and later on it was observed that supercritical fluids have promising solvating ability which may be dependent on the pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The gas is circulated on its own in the system without the need for a pump, as required in case of the supercritical CO 2 system. Moreover, the SubCO 2 system works at low temperature (<31 °C), low pressure (<7.1 MPa), and requires lesser mechanical parts (unlike supercritical CO 2 ) and, furthermore, residual solvent removal is not required [ 11 ]. The objectives of the current research work include isolation and recovery of bioactive compounds (phenolic, flavonoids, anthocyanins and carotenoids) from seeds of four different date varieties using conventional (Soxhlet) organic solvent-based and environment friendly SFE and SubCO 2 (both using CO 2 as extraction solvent) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The epoxide ring opening, which is catalysed by a base, transforms it to a hydrophobic alkylglycerol, which may then be grafted onto polysaccharide-free hydroxyl groups to produce hydrophobically grafted polysaccharides [ 32 ]. α-arbutin, a hydrophilic antioxidant and topical tyrosinase inhibitor, was used as a model drug following studies reporting its poor skin permeability due to the high hydrophilicity of the compound despite being considered as one of the most efficient whitening agents [ 33 , 34 , 35 ]. Different studies have lately sought to study the efficient percutaneous administration of α-arbutin, both topically and transdermally, to enhance its skin permeability due to its wide variety of uses in various applications [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%